2014
DOI: 10.1155/2014/824594
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hybridization on the Volatile and Sensorial Profile ofOcimum basilicumL.

Abstract: The aim of the present study was to investigate the volatile and sensorial profile of basil (Ocimum basilicum L.) by quantitative descriptive analysis (QDA) of the essential oil of three hybrids (“Cinnamon” × “Maria Bonita,” “Sweet Dani” × “Cinnamon,” and “Sweet Dani” × “Maria Bonita”). Twelve descriptive terms were developed by a selected panel that also generated the definition of each term and the reference samples. The data were subjected to ANOVA, Tukey's test, and principal component analysis. The hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Using the MFA it is also possible to explore the roles of the essential oil components. Our results are in confidence with previous studies (Da Costa et al, 2014), that GC-MS and sensory analysis showed good correlations, and some sensory parameters can be described by the relevant chemical components.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Using the MFA it is also possible to explore the roles of the essential oil components. Our results are in confidence with previous studies (Da Costa et al, 2014), that GC-MS and sensory analysis showed good correlations, and some sensory parameters can be described by the relevant chemical components.…”
Section: Discussionsupporting
confidence: 93%
“…vars/genotypes only minimal data is available (Da Costa et al, 2014). Therefore, our aim was to compare the semi-quantitative (relative % composition of essential oil) and qualitative parameters of aroma profiles of O. basilicum L. cultivars/genotypes by using GC-MS and sensory analysis.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oils can be classified in four chemotypes according to the main components: linalool-methyl chavicol, methyl chavicol, methyl cinnamate, and eugenol (Martins et al, 2010). There is variability of chemical composition since different chemotypes have been found in diverse regions of the world (Hassanpouraghdam et al, 2010), and they are classified according to their aroma in categories, such as sweet, lemon, cinnamon, camphor, anise, and cloves (Costa et al, 2014). The presence of essential oils with distinct constituents determines the specific aroma and flavor of basil and, consequently, its industrial potential.…”
Section: Introductionmentioning
confidence: 99%
“…It also contained methyl cinnamate, which was not found in any other cultivar in the study (Klimankova et al, 2008). Santos da Costa et al (2014) discovered that genetic hybrids of multiple basil varieties produce new aromas, and in one case, the previously unobserved in basil aroma compound (E)-caryophyllene.…”
Section: Basilmentioning
confidence: 99%